Incidence, patterns, risk factors and clinical outcomes of intravenous acyclovir induced nephrotoxicity - Abdullah M. Al-Alawi; Juhaina Salim Al-Maqbali; Maria Al-Adawi; Anan Al-Jabri; Henrik Falhammar (Elsevier, 2022)
Objectives: Acyclovir is approved to treat herpes simplex virus (HSV) type 1, type 2 and varicella-zoster virus. It is mainly eliminated via the kidneys, for which drug crystals accumulation might lead to nephrotoxicity. This study aimed to determine the incidence, risk factors, preventive measures, and clinical outcomes of acyclovir induced-nephrotoxicity. Methods: This is a retrospective cohort study of patients >12 years of age at Sultan Qaboos University Hospital (SQUH) receiving IV acyclovir therapy between January 2016 and December 2020. Results: Out of 191 included patients, 40 (20.1%) developed acyclovir induced-nephrotoxicity. Age (per year older: OR 1.04, 95 %CI 1.01-1.07), total duration of treatment (per day OR1.19, 95 %CI 1.06-1.33), and concomitant use of vancomycin (OR 5.96, 95 %CI 1.87-19.01) were significant independent risk factors for acyclovir induced-nephrotoxicity development. Nine patients (4.5%) died during the same hospitalization, including those three patients who required renal replacement therapy (1.5%). Conclusion: Frequent monitoring of kidney function for older patients with concurrent use of vancomycin and IV hydration is essential to prevent IV acyclovir induced-nephrotoxicity. Antimicrobial stewardship is a crucial method to reduce the duration of treatment with IV acyclovir as appropriate.